The Influence of Social Media Marketing Activities through Commitment, Trust, and Satisfaction on Customer Loyalty - Mohammad Farrel Uthman; Andhalia Liza Marie (Jurnal Manajemen dan Kewirausahaan, 2025)
In the rapidly evolving landscape of digital commerce, businesses are increasingly leveraging online platforms to connect with consumers in more personalized and interactive ways. Businesses can engage with customers and build long-term relationships through social media in today's digital age. Understanding how social media marketing activities influence user behavior is crucial for e-commerce platforms to maintain customer loyalty. The purpose of this study is to examine the influence of social media marketing activities on Tokopedia user loyalty through commitment, trust, and satisfaction, using both primary and secondary data collected through questionnaires. The sampling method employed is non-probability sampling with a purposive sampling technique, with a total of 257 respondents. The results of the study indicate that: (1) Social media marketing activities have a significant effect on commitment, trust, satisfaction, and customer loyalty; (2) Social media marketing activities have a significant effect on customer loyalty; and (3) Social media marketing activities have a significant effect on customer loyalty through commitment, trust, and satisfaction.